2021
DOI: 10.3390/cells10040900
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Bacterial Biologics Promotes Healthy Aging and Traumatic Brain Injury Responses in Adult Drosophila, Modeling the Gut–Brain Axis and Inflammation Responses

Abstract: Drosophila are widely used to study neural development, immunity, and inflammatory pathways and processes associated with the gut–brain axis. Here, we examine the response of adult Drosophila given an inactive bacteriologic (IAB; proprietary lysate preparation of Lactobacillus bulgaricus, ReseT®) and a probiotic (Lactobacillus rhamnosus, LGG). In vitro, the IAB activates a subset of conserved Toll-like receptor (TLR) and nucleotide-binding, oligomerization domain-containing protein (NOD) receptors in human cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…Emerging evidence suggests that autophagy may also be involved in gut-brain axis function that has been associated with GI and neuronal disease. 227,228 It was reported that the autophagy inducer trehalose may exert neuroprotective effects through microbiota-gut-brain signaling. 229 In Drosophila, feeding AD flies with acid bacteria can reverse AD phenotype and improve gut microbiota profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that autophagy may also be involved in gut-brain axis function that has been associated with GI and neuronal disease. 227,228 It was reported that the autophagy inducer trehalose may exert neuroprotective effects through microbiota-gut-brain signaling. 229 In Drosophila, feeding AD flies with acid bacteria can reverse AD phenotype and improve gut microbiota profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the LAB showed greater benefits in regulating mild TBI-related responses than probiotics, given that different treatments lead to different pathogen associated molecular pattern (PAMP) activity in adults fly. [66] Postbiotics has also been subjected to clinical trials in humans with some encouraging results. Heat-inactivated Lactobacillus gasseri CP2305 significantly ameliorates anxiety and sleep disturbance, and regulates stress-related microbiota on chronic stress responses adults in Japan.…”
Section: Postbioticsmentioning
confidence: 99%
“…In addition, the LAB showed greater benefits in regulating mild TBI‐related responses than probiotics, given that different treatments lead to different pathogen associated molecular pattern (PAMP) activity in adults fly. [ 66 ]…”
Section: Potential Bio‐materials Having Therapeutic Effects On Mddmentioning
confidence: 99%
“…10,11 Previously, in vivo Drosophila studies also showed lower basal levels of NF-κB gene targets upon IAB administration, further supporting this conclusion. 12…”
Section: Innate Immune Receptor Activationmentioning
confidence: 99%
“…10,11 Recently, it has been demonstrated through in vivo Drosophila studies that an inactive bacterial biologic (IAB), accompanied with confirmed pathogen molecular associated patterns (PAMPs) to select Toll-like receptors (TLR) and nucleotide-binding oligomerization domain-containing protein (NOD) receptors, lowered the inflammatory targets of the NF-κB signaling cascade. 12 A pilot study was conducted to determine the effect of oral administration of IAB on the systemic OS levels in humans using the OS biomarker, urinary F2-isoprostane (F2-IsoP). F2-IsoP is a stable noninvasive biomarker and an end-stage metabolite of prostaglandin oxidation, present in all fluids and tissues, and has been reported to increase during the oxidative injury (Mayo Clinic Labs; Cleveland Heart Lab, Inc.).…”
Section: Introductionmentioning
confidence: 99%